Nutrients removal and bacterial community structure for low C/N municipal wastewater using a modified anaerobic/anoxic/oxic (mA2/O) process in North China. (November 2017) - Zhang, Shihua; Huang, Zhijia; Lu, Shujian; Zheng, Jun; Zhang, Xinxi
Graphical abstract: Highlights: A modified anaerobic/anoxic/oxic process (mA2/O) was proposed. Nutrients removal and bacterial community characteristics were investigated. The 13 dominant genera were shared by the five functional zones. Low temperature influenced growth of Nitrosomonas, Nitrosospira, PAOs and GAOs. DO played more important roles in regulating bacterial community composition than HRT. Abstract: A modified anaerobic/anoxic/oxic (mA2/O) process based on utilizing the internal carbon source and adding polypropylene carriers was operated for 90 d to investigate the nutrients removal performance and bacterial community. This system exhibited a stable and efficient performance, particularly, in removing the NH4 + -N and total phosphorus. The results of high-throughput sequencing showed that the 13 dominant genera containing Pseudomonas, Comamonas, Arcobacter, Nitrobacteria, Nitrosospira, Nitrosomonas, Bacteroides, Flavobacterium, Rhizobium, Acinetobacter, Zoogloea, Rhodocyclus and Moraxella were shared by five zones, inferring that they were the essential players in treating low C/N (below 5.0) municipal wastewater around 10 °C. The average abundance of Nitrosospira (4.21%) was higher than that of Nitrosomonas (2.93%), suggested that Nitrosospira performed well under low temperature for nitrification. Additionally, both known Rhodocyclus -related PAOs and GAOs Competibacter were not detected possibly due to low temperature. Redundancy analysis (RDA) indicated that DO played more important roles in regulating bacterial community composition than HRT.